Excellent Mechanical Durability of In‐Folding Stress of Poly‐Si Thin‐Film Transistor on Plastic Substrate Compared with Out‐Folding: Generation of Gate Leakage Currents in Flexible Poly‐Si Thin‐Film Transistor by Out‐Folding and Bias‐Temperature Stress - Kim, Dongjin; Billah, Mohammad Masum; Lee, Suhui; Siddik, Abu Bakar; Cho, Young Joo; Jang, Jin; Lee, Jaeseob; Lee, Yongsu; Shin, Jiyeong (Advanced engineering materials, 2021)
The effect of electro‐thermal stress on the electrical performance of flexible, low‐temperature polysilicon (LTPS) thin‐film transistors (TFTs) after mechanical‐folding stress aiming to improve the reliability of foldable display backplanes is studied (IG). Herein, for the first time, the significant increase of gate leakage currents upon the negative bias temperature stress (NBTS) or positive bias temperature stress (PBTS) after the out‐folding test on excimer laser annealing (ELA) TFTs is reported. Out‐folding stress increases the drain current, shifts the threshold voltage (ΔVTH) by 2.4 V, and increases the subthreshold swing without affecting the (IG). However, the ΔVTH is 1.8 V upon NBTS, and the negative ΔVTH is −4.7 V upon PBTS after out‐folding stress along with a drastic increase in IG. A thermal annealing at 250 °C for 10 h for the electro‐thermal stressed TFTs after out‐folding is performed, and initial electrical characteristics recovery is achieved; except the abruptly increased IG. These results are correlated with charge trapping at the damaged grain boundary and (GI). A model with moisture/water molecule diffusion through the nanocracks generated by out‐folding is proposed. The ionized charges (H+, OH−) captured at the nanocrack‐induced trap sites in poly‐Si and GI appear to be the origin of abnormal ΔVTH and IG. A big difference between in‐folding and out‐folding of the poly‐Si thin‐film transistor (TFT) on polyimide (PI) is found. The change in threshold voltage by in‐folding stress is much smaller than that by out‐folding. The significant increase of gate leakage currents (IG) is observed combined effect of out‐folding and positive bias temperature stress (PBTS). But, in‐folding exhibits stable (IG).